Project Based Learning (PBL) Implementation for Improving Japanese Language Grammar Competence in Virtual Classroom - Sukmara, Rina (Universitas Pendidikan Indonesia (Indonesia University of Education), 2021)
This study aims to determine the implementation and improvement of learning outcomes in the virtual classroom method through Project Based Learning (PBL) method on learning Japanese grammar. The application of PBL in virtual classrooms is an alternative for active learning. Virtual classroom is one form of learning space that applies the use of current technology to shorten and eliminate distance and space, where learning is able to be carried out through social media. PBL itself emphasizes the learnerâ€™s ability to apply learning into daily life through certain projects. This study uses a quasi-experimental method. The sample or data source of this research was students in semester 3 of the Japanese Language Education Study Program at one of the private universities in Jakarta. Based on the Mann Whitney test using SPSS 25, the sig value was 0.001. Because the value of sig = 0,000 0.005, there is a significant difference between the pre-test and post-test values between before and after the application of the virtual classroom method through PBL. Based on the results of the gain in pre-test and post-test values, the result was 17%.Â So it can be concluded that PBL implementation in the virtual classroom cannot increase the value of learning outcomes in learning Japanese grammar.